Design Recommendations for a Child-Oriented Christian Education App Based on Usability Evidence - Henoch Juli Christanto (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Technology has become a routine part of children's learning, including the transmission of religious values through mobile applications. This study evaluates the usability of the Superbook Kids Bible App — a child-oriented Christian learning application — using Nielsen's five usability dimensions: learnability, efficiency, memorability, errors, and satisfaction. A descriptive quantitative survey was conducted with 100 respondents selected through purposive sampling, with sample size determined by Slovin's formula at a 10 percent margin of error. A 25-item questionnaire was validated using Pearson item-total correlations, yielding validity coefficients ranging from 0.598 to 0.824, while reliability testing confirmed good internal consistency. Descriptive results indicate moderate overall usability, with mean scores of 22.40 for learnability, 8.12 for efficiency, 8.65 for memorability, 17.76 for errors, and 14.91 for satisfaction. Category analysis identifies efficiency as the primary bottleneck, with 46 percent of respondents in the low category, followed by learnability at 33 percent, while errors were predominantly moderate at 60 percent. Based on these findings, the study proposes evidence-based design priorities: performance improvements to reduce loading and response delays, streamlined navigation to cut unnecessary steps, and guided onboarding with child-appropriate prompts to support early-stage learnability, alongside clearer feedback and error recovery mechanisms. Future research should combine task-based observation with usage analytics, test interventions such as gamification and personalization, and apply longitudinal designs to examine sustained engagement and learning outcomes in faith-based mobile learning.